Design and Construction of a Novel Micro-Extrusion System for Bio-printing Applications - Levent AYDIN; Assoc. Prof. Serdar KÜÇÜK; Assoc. Prof. Halime KENAR (International Journal of Applied Methods in Electronics and Computers, 2016)
Three-dimensional (3d) bio-printing is one of the major research fields of future, as yet at the beginning stage but producing promising solutions in medicine. As technology evolves, novel systems emerge for positioning even a single cell to the desired place to create functional tissues. The precision of these systems determine the functionality of outputs. In general, bio-printers use Ink-jet, Micro-extrusion and Laser Assisted printing methods to construct a solid tissue or a part of an organ. Ink-jet method, also known as drop-on-demand bio-printing approach, is based on spraying cells by means of thermal or piezo electric pulses from numerous nozzles and is commonly used when forming tissues like skin and cartilage. Micro-extrusion method is used when complex biological structures like blood vessels or solid organs are bio-printed. Laser Assisted method is more preferred for biomaterial or implant production. Components of these systems have direct effects on the output since they determine where and how much biological material will be deposited in every layer. The aim of this study is to design and construct a novel micro-extrusion module for bio-printing applications. The designed module consists of three-dimensional (3d) printed body parts from Polylactic acid (PLA), Nema type stepper motors, ball screws (SFU1204), ball screw nuts (M12), flexible couplings (5 x 8 x 25 mm), steel rods (M8), SCE UU series bearings (SCE 8 UU), UFL series bearings (UFL 08), LMEF series bearings (LMEF 8 UU), SK series rod holders (SK 08) and has an ability to control three commercially available syringes with blunt ended needles. For precise micro-extrusion, galvanized steel rods support ball screw driven linear motions. Ergonomically, syringes can be easily mount and locked and this system also has laser holders that can be used for targeted photo polymerization.